CHE680: Leadership and Professional Ethics for Engineers / College of Engineering - UiTM, College of Engineering (2023)
Leadership and Professional Ethics for Engineers is designed to introduce engineering students to the concepts, theory and practice of engineering leadership; engineering leadership characteristics, individual differences and self-awareness; developing and building teams; managing change, conflicts, and crises; and understanding real-world ethics and core values. This course is designed to contain two (2) parts. The first part concentrates on major theories of leadership and detailed study of the “Thoughts and Policies of Tun Dr. Mahathir Mohamed”. The second part incorporates “Engineers in Society” syllabus of The Institute of Engineers (Malaysia). In addition, students will be exposed to the professional ethics concepts that can be applied in real engineering world.